Feedbacks of plant identity and diversity on the diversity and community composition of rhizosphere microbiomes from a long‐term biodiversity experiment - Schmid, Marc W.; Hahl, Terhi; Moorsel, Sofia J.; Wagg, Cameron; De Deyn, Gerlinde B.; Schmid, Bernhard (Molecular ecology, 2019)
Soil microbes are known to be key drivers of several essential ecosystem processes such as nutrient cycling, plant productivity and the maintenance of plant species diversity. However, how plant species diversity and identity affect soil microbial diversity and community composition in the rhizosphere is largely unknown. We tested whether, over the course of 11 years, distinct soil bacterial communities developed under plant monocultures and mixtures, and if over this time frame plants with a monoculture or mixture history changed in the bacterial communities they associated with. For eight species, we grew offspring of plants that had been grown for 11 years in the same field monocultures or mixtures (plant history in monoculture vs. mixture) in pots inoculated with microbes extracted from the field monoculture and mixture soils attached to the roots of the host plants (soil legacy). After 5 months of growth in the glasshouse, we collected rhizosphere soil from each plant and used 16S rRNA gene sequencing to determine the community composition and diversity of the bacterial communities. Bacterial community structure in the plant rhizosphere was primarily determined by soil legacy and by plant species identity, but not by plant history. In seven of the eight plant species the number of individual operational taxonomic units with increased abundance was larger when inoculated with microbes from mixture soil. We conclude that plant species richness can affect below‐ground community composition and diversity, feeding back to the assemblage of rhizosphere bacterial communities in newly establishing plants via the legacy in soil.